Images Of Revelation In The Narrations Of Ahl Al-Bayt (Peace Be Upon Them( (Journal of the College of Basic Education, 2024)
The only source and source of revelation is from God Almighty, and if we contemplate the verses of the Holy Qur’an, we will find a diversity in the forms of revelation, as the Holy Qur’an used words that emphasize the diversity of its forms, and through them, scholars deduced from them the sections of revelation, and this research was devoted to explaining the narrations of Ahl al-Bayt (peace be upon them( which explained how the revelation was sent down to the Noble Prophet (may God’s prayers and peace be upon him and his family) and its forms, as well as the sections and conditions of the revelation according to the narrations of the Ahl al-Bayt (peace be upon them).